PENGARUH JENIS OLI TERHADAP DAYA DAN KONSUMSI BAHAN BAKAR MOTOR KAPASITAS 150 CC - Rasta Purba; Kristian Tarigan (JURNAL ILMIAH TEKNIK SIPIL, 2020)
Analysis of the effect of the use of oil types on fuel consumption and power aims to compare the value of viscosity to fuel consumption and the power produced, the method used is an experimental tru method that is investigating the possibility of cause and effect by controlling. As a result of a number of variations in the type of oil on fuel consumption and power produced by a 150 CC combustion motor capacity, research conducted with SUZUKI FU 150 material obtained fuel values ​​with a measuring cup and power values ​​with a dynamometer test equipment. Variation in oil viscosity affects fuel consumption, the higher the viscosity value, the higher the fuel consumption is seen from Figure 5.1. above shows that at rotation of 5000 rpm SAE 10W-60 shows that the highest fuel consumption is 0.091 gr / sec while at the same rotation the 5000 rpm SAE 10W-30 has the least fuel consumption value at 0.0455 gr / sec, that the level of oil viscosity affects the power generated, where the power produced is inversely proportional to the level of oil viscosity, the decrease in power as oil viscosity increases, the power decreases at each rotation variation, the power decreases at a maximum rotation of 22.8 at SAE 10W, and the numbers continue to decline to the point of 20.63 at SAE 10-60, likewise at 7000 Rpm rotation and at 5000 rpm at SAE 10W-30 at 9.5 point decreased to 7.03 using SAE 10W-60 , the table shows the thicker oil used the lower the power generated.